2010
DOI: 10.1088/0952-4746/30/2/s07
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the radiation exposure of terrestrial wildlife in the Chernobyl exclusion zone: an international comparison of approaches

Abstract: There is now general acknowledgement that there is a requirement to demonstrate that species other than humans are protected from anthropogenic releases of radioactivity. A number of approaches have been developed for estimating the exposure of wildlife and some of these are being used to conduct regulatory assessments. There is a requirement to compare the outputs of such approaches against available data sets to ensure that they are robust and fit for purpose. In this paper we describe the application of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…); and k r , em is the effective loss rate of radionuclide "r" from mammal (day À1 ) incorporating both excretion rate and physical decay of the radionuclide. These types of models have been applied, albeit for a limited suite of radionuclides, within international inter-comparison exercises (Beresford et al, 2010) and indicate that the approach provides reasonable predictions of transfer to wild mammals in natural terrestrial environments. On a more negative note, these types of models require much greater parameterisation than the more commonly used CR approach and, in many cases, parameter values are simply unavailable.…”
Section: Transfer Between Food Source and Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…); and k r , em is the effective loss rate of radionuclide "r" from mammal (day À1 ) incorporating both excretion rate and physical decay of the radionuclide. These types of models have been applied, albeit for a limited suite of radionuclides, within international inter-comparison exercises (Beresford et al, 2010) and indicate that the approach provides reasonable predictions of transfer to wild mammals in natural terrestrial environments. On a more negative note, these types of models require much greater parameterisation than the more commonly used CR approach and, in many cases, parameter values are simply unavailable.…”
Section: Transfer Between Food Source and Mammalsmentioning
confidence: 99%
“…This yields an IR value for bank vole of 1.14 d À1 . No direct empirical data in relation to fresh matter ingestion rates for common shrew are available in Nagy (2001), but by assuming a mass of 10 g for an adult shrew (Beresford et al, 2010) and by applying the allometric relationship as shown in Eq.…”
Section: Transfer Between Food Source and Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent international evaluations of the available models have shown this to be the case (Vives i Batlle et al 2007Beresford et al 2008aBeresford et al , 2010aYankovich et al 2010a). There are many reasons for this including lack of empirical data for many radionuclide-organism combinations and the theoretical approaches used to derive transfer values when no data exist; use of national data sets; and the conservative nature of some of the parameter values selected to meet the purpose of specific tools (Beresford et al 2008aYankovich et al 2010a).…”
mentioning
confidence: 94%
“…This simplified model was thereafter used to make predictions of activity concentrations in wild animals in terrestrial environment and appears to yield reasonable results in the sense that for most radionuclides and animals where predictions were made, results were not substantially different from those predicted using more conventional concentration ratio based approaches [2]. The model is represented in the form of an interaction matrix as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%